Pistas de contextualização nos avisos em AVA: uma contribuição para o ensino de Língua Portuguesa na modalidade a distância - Andrade, Débora Cristina Longo (2015)
This dissertation has as its object of study of contextualization cues on a corpus consisting of notices, written and directed by the teacher to students in the Virtual Learning Environment (VLE), seeking to understand how, in this context, the cues contribute, in the course of interaction, for processing and building meaning of the text. For this purpose, we selected fifteen notices for Written Communication Distance, taught entirely online by a private institution of higher learning in the city of São Paulo. Notices are analyzed on the basis of studies of text and context performed in the fields of Textual Linguistics and Interactional Sociolinguistics. Obtained by methodological procedures focused on a qualitative approach, the results indicate that the contextualization cues in the notices serve as an important strategy for situating students regarding topics of study, establish proximity and student involvement with the activities performed in the distance course